2015
DOI: 10.1586/17434440.2015.1080119
|View full text |Cite
|
Sign up to set email alerts
|

Absorb bioresorbable stents for the treatment of coronary artery disease

Abstract: Bioresorbable stents are considered to be the 'fourth revolution' in percutaneous coronary intervention. The first clinically available Absorb(®) bioresorbable device is made of poly-l-lactic acid polymer and elutes everolimus. The process of bioresorption is completed in 3 years. The introduction of this device into clinical practice went through several logical phases: first-in-man studies, randomized Absorb II study with moderately complex patients and lesions, registries of real life patient population and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…From equation (13), it is observed that F e1 decreases with the increase of θ, which is about half of the strut angle β. erefore, under the same elastic recoiling force F e , the supporting element with the larger strut angle at the inflated state will undergo a lower circumferential force F e1 . Furthermore, based on the discussion in Section 2.1 as well as the previous discussion in this section, the strut angle of the small supporting element at the inflated state is larger for the OCS than that for the BVS.…”
Section: Finite Element Analysis Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From equation (13), it is observed that F e1 decreases with the increase of θ, which is about half of the strut angle β. erefore, under the same elastic recoiling force F e , the supporting element with the larger strut angle at the inflated state will undergo a lower circumferential force F e1 . Furthermore, based on the discussion in Section 2.1 as well as the previous discussion in this section, the strut angle of the small supporting element at the inflated state is larger for the OCS than that for the BVS.…”
Section: Finite Element Analysis Resultsmentioning
confidence: 99%
“…Apart from the modification of build materials [10,11], two strategies have been developed to improve the mechanical properties of BPSs: (1) increasing strut thickness [12][13][14] and (2) changing stent structure. For the former one, the increase of strut thickness can effectively improve the radial force, while it also results in the increase of the entire profile, which leads to the increasing risk of in-stent restenosis and limits the treatments for heavily curved or highly calcified diseased vessels [15].…”
Section: Introductionmentioning
confidence: 99%
“…At first, proximal and distal scaffold markers were identified on the OCT pullback. The design of Absorb ™ BRS is such, that the scaffold edges extend beyond the markers by 0.3 mm at the distal end and by 0.9-1.3 mm at the proximal end [15]. We have therefore measured proximal and distal reference vessel area and mean diameter as a mean value of frames at the distance between 2 and 5 mm from the scaffold markers ( Fig.…”
Section: Oct Acquisition and Analysismentioning
confidence: 99%
“…2). Balloon angioplasty, pioneered by Andres Grüntzig in 1977, was the first procedure by which medical professionals were able to intervene non-surgically in order to establish coronary revascularization (Gruntzig 1978;Simard et al 2014;Kočka et al 2015). This method was found to be effective in initiating patency to a narrowed or blocked artery; however, severe life-threatening risks were also associated with it as a result of a high threat of restenosis (occurrence of vessel blockage triggered by arterial remodelling and intima hyperplasia) due to coronary dissection and arterial recoil (Oberhauser et al 2009;Serruys et al 2012;Bourantas et al 2013;Simard et al 2014;Kočka et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The development of coronary stents began in the 1980s as a means to overcome the restenosis issues related to balloon angioplasty (Hoffmann and Mintz 2000;Kočka et al 2015). This scheme is based on the introduction of scaffolding of the artery with balloon inflated metallic stents averting early constrictive remodelling, stabilizing vascular dissections and eliminating arteral recoil.…”
Section: Introductionmentioning
confidence: 99%